Oxidative Stress Related to Iron Metabolism in Relapsing Remitting Multiple Sclerosis Patients With Low Disability - Siotto, Mariacristina; Filippi, Maria Maddalena; Simonelli, Ilaria; Landi, Doriana; Ghazaryan, Anna; Vollaro, Stefano; Ventriglia, Mariacarla; Pasqualetti, Patrizio; Rongioletti, Mauro Ciro Antonio; Squitti, Rosanna; Vernieri, Fabrizio (Frontiers in Neuroscience, 2019)
Oxidative status may play a role in chronic inflammation and neurodegeneration which are considered critical etiopathogenetic factors in Multiple Sclerosis (MS), both in the early phase of the disease and in the progressive one. The aim of this study is to explore oxidative status related to iron metabolism in peripheral blood of stable Relapsing-Remitting MS with low disability. We studied 60 Relapsing-Remitting MS patients, (age 37.2 ±9.06, EDSS median 1.0) and 40 healthy controls (age 40.3±10.86). We measured total hydroperoxides (dROMs test) and Total Antioxidant Status (TAS), along with the iron metabolism biomarkers: Iron (Fe), ferritin (Ferr), transferrin (Tf), transferrin saturation (Tfsat) and Ceruloplasmin (Cp) panel biomarkers [concentration (iCp) and enzymatic activity (eCp), copper (Cu), ceruloplasmin specific activity (eCp:iCp), copper to ceruloplasmin ratio (Cu:Cp), non-ceruloplasmin copper (nCp-Cu)] . We computed also the Cp:Tf ratio as an index of oxidative stress related to iron metabolism. We found lower TAS levels in MS patients than in healthy controls (CTRL) and normal reference level and higher dROMs and Cp:Tf ratio in MS than in healthy controls. Cp and Cu were higher in MS while biomarkers of iron metabolism were not different between patients and controls. Both in controls and MS, dROMs correlated with iCp (CTRL r=0.821, p<0.001; MS r=0.775 p<0.001) and eCp (CTRL r=0.734, p<0.001; MS r=0.820 p<0.001). Moreover, only in MS group iCp correlated negatively with Tfsat (r= -0.257, p=0.047). Dividing MS patients in “untreated” group and “treated” group, we found a significant difference in Fe values (F(2, 97)=10.136, p<0.001); in particular “MS untreated” showed higher mean values (mean = 114.5, sd=39.37 µg/dL) than CTRL (mean 78.6, sd=27.55 µg/dL p=0.001) and “MS treated” (mean=72.4, sd=38.08 µg/dL; p<0.001). Moreover, “MS untreated” showed significantly higher values of Cp:Tf, (mean=10.19, sd=1.77*10-2; p=0.015) than CTRL (mean= 9.03, sd=1.46 *10-2). These results suggest that chronic oxidative stress is relevant also in the remitting phase of the disease in patients with low disability and short disease duration. Therefore, treatment with antioxidants may be beneficial also in the early stage of the disease to preserve neuronal reserve.